Bioinspired interfacial engineering for highly stretchable electronics - Osman Gul; Myoung Song; Chang-Yeon Gu; Jihyeon Ahn; Kichul Lee; Junseong Ahn; Hye Jin Kim; Taek-Soo Kim; Inkyu Park (Nature Communications)
Abstract The seamless integration of rigid/flexible electronic components into stretchable substrates is imperative for the realization of reliable stretchable electronics. However, the transition from flexible-to-stretchable substrates presents inherent challenges in interfacial behavior, predominantly arising from disparities in elastic moduli, thereby rendering their integration arduous for practical deployment. Here, we introduce a bioinspired interface-engineered flexible island (BIEFI), which effectively facilitates the creation of highly stretchable electronics by optimizing the interface with flexible mechanical interlocking mechanisms, resilient to physical deformations. Various electronic components, such as light-emitting diodes (LEDs) and solar cells, are affixed onto the flexible island, showcasing its versatility as a robust platform for rigid components while ensuring the entire substrate maintains high stretchability. Additionally, a smart workout monitoring system is demonstrated by integrating a resistance band with a flexible-to-stretchable platform. This approach seamlessly integrates a wide range of rigid, flexible, and stretchable components, ensuring durability under diverse physical deformations.